2010
DOI: 10.1111/j.1365-3083.2010.02378.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the Involvement of Galectin-3 in Mesenchymal Stem Cell Suppression of Allogeneic T-Cell Proliferation

Abstract: Human bone marrow‐derived mesenchymal stem cells (MSC) are multipotent non‐hematopoietic progenitors that have regulatory activity on immune cells. NOD‐ and Toll‐like receptors (NLR, TLR) have several roles in immunity, including those relevant to pathogen recognition and shaping the course of immune responses by controlling gene expression. We have shown that these innate immune receptors are expressed by hematopoietic CD34+ progenitors and MSC. To uncover genes critical in MSC function, first we have used mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
102
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(106 citation statements)
references
References 28 publications
3
102
0
1
Order By: Relevance
“…Wang et al [202] hypothesized that hypoxia or TNFα activates MSCs which are able to release VEGF by STAT3 and p38 MAPK dependent mechanisms. Human MSCs that released VEGF in response to TLR-2 and NOD-1 ligands were also described [203] .…”
Section: Vascular Endothelial Growth Factormentioning
confidence: 99%
“…Wang et al [202] hypothesized that hypoxia or TNFα activates MSCs which are able to release VEGF by STAT3 and p38 MAPK dependent mechanisms. Human MSCs that released VEGF in response to TLR-2 and NOD-1 ligands were also described [203] .…”
Section: Vascular Endothelial Growth Factormentioning
confidence: 99%
“…New evidence has shown the involvement of Galectin-3 as a regulator of MSCs immunosuppression function inhibiting allogeneic T cell proliferation by MSCs (Sioud 2011). This group demonstrated that gene knockdown of Galectin-3 resulted in less immunosuppressive effect on T cell proliferation (Sioud, Mobergslien et al 2010). Galectins were also shown to regulate the secretion of proinflammatory cytokines and promote expansion of IL-10 producing peripheral Tregs (Sioud 2011).…”
Section: Mscs-galectins and Immunosuppression Inductionmentioning
confidence: 95%
“…Recently, Sioud et al (Sioud, Mobergslien et al 2010;Sioud 2011)and Gieseke et al (Gieseke, Bohringer et al 2010) have described another mechanism of MSCs immunosuppression that involves a family of beta galactosidase-binding proteins named Galectins which are involved in immune tolerance (Garin, Chu et al 2007). It has been demonstrated that Galectin-1, Galectin-3, Galectin-8 and Galectin-9 are constitutively expressed by human bone marrow MSCs with Galectin-1 and Galectin -3 being further secreted and expressed on the outer plasma membrane (Wada and Makino 2001).…”
Section: Mscs-galectins and Immunosuppression Inductionmentioning
confidence: 99%
“…Sioud et al [47] showed that Gal-3 can modulate MSCs immunosuppressive activity on T-lymphocyte proliferation. High levels of Gal-3 protein are found in MSCs culture supernatants; thus, it may participate in extra cellular matrix (ECM)-cell interactions and modulation of surrounding immune cells.…”
Section: Galectins (Gal)mentioning
confidence: 99%